DEIXIS IN MOANA MOVIE - rina anggi puspita; Rina Anggi p, Yola Merina Dian Noviani Syafar (FKIP Universitas Citra Bangsa, 2022)
This study aims to analyze the types of Deixis in the Moana movie by using Cruse's (2006) theory. The researcher chose a dialogue between Moana and Maui. Therefore, this research was conducted using observational method with non participant observational technique . The data used are film dialogues and scripts which are classified into types of deixis based on their criteria. The results showed that the researcher found five deixis in the film, namely personal deixis, spatial deixis, temporal deixis, discourse deixis and social deixis, with details of 133 persona deixis, 39 spatial deixis, 4 temporal deixis, 12 discourse deixis and 20 social deixis from Moana's utterances. The researcher also found 151 person deixis, 43 spatial deixis, 7 temporal deixis, 12 discourse deixis and 24 social deixis according to Maui's utterances. And that the type of persona deixis appears the most in this study